'To die, to sleep' – assisted dying legislation in Victoria: A case study. (November 2019) - Gilbert, Julia; Boag, Jane
Background: Assisted dying remains an emotive topic globally with a number of countries initiating legislation to allow individuals access to assisted dying measures. Victoria will become the first Australian state in over 13 years to pass Assisted Dying Legislation, set to come into effect in 2019. Objectives: This article sought to evaluate the impact of Victorian Assisted Dying Legislation via narrative view and case study presentation. Research design: Narrative review and case study. Participants and research context: case study. Ethical considerations: This legislation will provide eligible Victorian residents with the option to request access to assisted dying measures as a viable alternative to a potentially painful, protracted death. Findings: This legislation, while conservative and inclusive of many safeguards at present, will form the basis for further discussion and debate on assisted dying across Australia in time to come. Discussion: The passing of this legislation by the Victorian parliament was prolonged, emotive and divided not only the parliament but Australian society. Conclusion: Many advocates for this legislation proclaimed it was well overdue and will finally meet the needs of contemporary society. Protagonists claim that medical treatment should not provide a means of ending life, despite palliative care reportedly often failing to relieve the pain and suffering of individuals living with a terminal illness.